Glorification of Masculinity in the Advertisements of Kool Shaving Cream/Foam: A Critical Discourse Analysis - Alam, Md. Mahbubul (Universitas Negeri Semarang, 2021)
Advertisement pervades our daily life with strong hold and affects our beliefs and psychological orientation extensively. It is a very effective podium for popularizing products as well as spreading ideologies. Advertisement is one of the dominant platforms of carrying discourses to the masses. The present study is an investigation done from a critical point of view of the advertisements of Kool shaving foam/cream by analyzing the speeches, linguistic and literary devices, character portrayal and physical setting of the advertisements. For the findings, analysis and discussion Critical Discourse Analysis (CDA) based on Fairclough’s Three Dimension Approach is applied. The analysis reveals that while circulating and advertising of Kool shaving foam/cream the advertisers have concurrently disseminated patriarchal ideologies and masculine discourses that have long been being lived out in our society as discursive practices. It is also found that at the end of each sample advertisement it is the veneration of masculinity, not the circulation of the product, which is significantly highlighted.